Modern contraceptive usage and its associated factors among Orang Asli women attending community clinics in East Pahang - Jamani, Nurjasmine Aida; Ahmad Zawawi, Muhammad Zul Hazmi; Kamaruzaman, Nor Azam; Pasi, Hafizah (2021)
❖ There is a high unmet need for modern contraception among Orang Asli women¹. Orang Asli women has high risk for maternal health related morbidity and morbidity. ❖ Modern contraceptive usage are proven able to reduce maternal health related morbidity and mortality, as well as improving the quality of life of women in general². ❖ The aim of this study is to determine the prevalence of modern contraceptive usage among Orang Asli women as well as its associated factors